2011
DOI: 10.1016/j.brainres.2010.10.056
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical distribution of WARP (von Willebrand A domain-related protein) in the inner ear

Abstract: The basic components of the epithelial, perineural and perivascular basement membranes in the inner ear have been well-documented in several animal models and in the human inner ear. The von Willebrand A domain-related protein (WARP) is an extracellular matrix molecule with restricted expression in cartilage, and a subset of basement membranes in peripheral nerves, muscle and central nervous system vasculature. It has been suggested that WARP have an important role in maintaining the blood-brain barrier. To da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 31 publications
1
7
0
Order By: Relevance
“…WARP‐immunoreactivity localized to the vasculature of the cochlea, stria vacularis, and vestibular apparatus with some co‐localization with smooth muscle actin. Consistent with an earlier study (Allen et al, ), WARP was detected in the vessels associated with neural tissue of the brainstem and cerebellar cortex (Duong et al, ).The authors speculate that WARP may have a structural or maintenance role of the blood vessels of the cochlea and vestibule.…”
Section: Tissue Expression Of Vwa1/warpsupporting
confidence: 90%
See 1 more Smart Citation
“…WARP‐immunoreactivity localized to the vasculature of the cochlea, stria vacularis, and vestibular apparatus with some co‐localization with smooth muscle actin. Consistent with an earlier study (Allen et al, ), WARP was detected in the vessels associated with neural tissue of the brainstem and cerebellar cortex (Duong et al, ).The authors speculate that WARP may have a structural or maintenance role of the blood vessels of the cochlea and vestibule.…”
Section: Tissue Expression Of Vwa1/warpsupporting
confidence: 90%
“…WARP was detected in the inner ear by immunohistochemistry in human autopsy specimens and in mice (Duong et al, ). WARP‐immunoreactivity localized to the vasculature of the cochlea, stria vacularis, and vestibular apparatus with some co‐localization with smooth muscle actin.…”
Section: Tissue Expression Of Vwa1/warpmentioning
confidence: 99%
“… (1) Present study, (2) Ishiyama et al (2009), (3) Lopez et al (2007), (4) Nadol et al (1993), (5) Robertson et al (2006), (6) Duong et al (2011), (7) Ying and Balaban (2009), (8) Markaryan et al (2009), (9) Ishiyama et al (1994), (10) Anniko et al (1989a), (11) Khalifa et al (2003), (12) Keithley et al (1995), (13) Schrott-Fischer et al (1994), (14) Liu et al (2009), (15) Takahashi et al (2010), (16) Popper et al (2002), (17) Yamashita et al (1991), (18) Yamashita et al (1992), (19) Shi et al (1992a, b), (20) Anniko et al (1989b), (21) Doherty and Linthicum (2004), (22) Keithley et al (2001), (23) Kong et al (1998), (24) Markaryan et al (2008c), (25) Ahmed et al (2013), (26) Balaker et al (2013), (27) Nguyen et al (2014), (28) Vorasubin et al (2016) +Tested and detected by IHC or IF (present study), − not detected in the present study, NR not reported …”
Section: Figmentioning
confidence: 99%
“…The characteristics and specificity of the antibodies used in this study have been described in detail (Duong et al 2011; Ishiyama et al 2009, 2010; Lopez et al 2005a, 2007a, 2009; Calzada et al 2012a, b; Balaker et al 2013; Ahmed et al 2013; Nguyen et al 2014; Vorasubin et al 2016) (Table 3). …”
Section: Immunofluorescencementioning
confidence: 99%
“…This likely reflects the severe degeneration of the endothelial cell. While isolectin IB4 identifies capillaries, small and medium sized arteries can be identified with von Willebrand A domain-related protein ( Duong et al, 2011 ). Similarly, in surgical normative acoustic neuroma, the IB4-IF was noted in red, with stellate, fingerlike pericyte processes in green ( Figure 4C ) but the Meniere’s specimen lacked IB4 fluorescence ( Figure 4D ).…”
Section: Resultsmentioning
confidence: 99%